Shaping Ability of WaveOne Gold Primary in combination with different glide path file systems in curved root canals - Kübra Yeşildal Yeter; Betül Güneş; İbrahim Şevki Bayrakdar (Selcuk Dental Journal)
ABSTRACTBackground:The purpose of this in-vitro study was to evaluate the centering ability and the apical transportation of curved root canals after preparation with WaveOne Gold single-file reciprocating system with guidance of different glide path systems by using Cone-Beam Computed Tomography. Methods:Seventy-two extracted mandibular first molar teeth with curved mesial roots were selected for this study. Specimens were randomly divided into six experimental groups according to the root canal preparation (n = 12): Group G-File; Group One G; Group ProGlider; Group PathFile; Group K-files; and Group control. After forming a glide path, root canal preparation procedure was completed with WaveOne Gold primary instrument (#25). Cone-beam computed tomographic images of specimens were taken before and after root canal preparation procedure. Apical transportation and centering ability were evaluated at 1, 4, and 7 mm from the apical foramen. The data were statistically analyzed using the Kruskal Wallis test at a significance level of P = 0.05. Results:There were no significant differences among all experimental groups. (p > 0.05) Conclusion:Creating a glide path in curved root canals with either NiTi glide path files or stainless still manuel K-files before root canal preparation with WaveOne Gold Primary caused similar apical transportation and centering ability results with no glide path used group.